1996
DOI: 10.1021/ja952540f
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium NMR Kinetic Measurements of Solvent Effects on the Bimolecular Electron Transfer Self-Exchange Rates of Ruthenium Ammine Complexes. A Dominant Role for Solvent−Solute Hydrogen Bonding

Abstract: Electron transfer self-exchange rate constants for a series of three ruthenium ammine complexes have been determined in a range of solvents using deuterium NMR line-broadening measurements. It is found for all three complexes that the observed rates slow dramatically in solvents of strong Lewis basicity as measured by the Gutman donor number. The rates do not correlate significantly with either the dielectric continuum-based Pekar factor, (1/n 2 -1/D s ), or the solvent longitudinal relaxation time known to fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…In contrast, in the case of a nonadiabatic (weak coupling) regime, the contribution of fast (elastic) degrees of freedom should be much larger compared to slow (relaxational) variables. , It is not surprising to observe different mechanisms of the elementary electron-transfer step, viz., weak and strong coupling regimes, for homogeneous and electrochemical processes, respectively, since parallel electron transitions to or from a band of states near the Fermi level may result in the total probability of electron transfer near 1 and thus in much stronger intersite electron coupling in the case of electrode processes compared to analogous homogeneous electron self-exchange . This conclusion is compatible also with the recent results on homogeneous and electrode electron exchange of ruthenium ammine complexes . In the heterogeneous electron-transfer case, rapid-scan cyclic voltammetric studies showed a correlation of electron-transfer rate with solvent longitudinal relaxation time, τ L , while deuterium NMR homogeneous self-exchange studies revealed no dependence of this kind, indicating a change to nonadiabatic from overdamped behavior upon going from the heterogeneous to the homogeneous process.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, in the case of a nonadiabatic (weak coupling) regime, the contribution of fast (elastic) degrees of freedom should be much larger compared to slow (relaxational) variables. , It is not surprising to observe different mechanisms of the elementary electron-transfer step, viz., weak and strong coupling regimes, for homogeneous and electrochemical processes, respectively, since parallel electron transitions to or from a band of states near the Fermi level may result in the total probability of electron transfer near 1 and thus in much stronger intersite electron coupling in the case of electrode processes compared to analogous homogeneous electron self-exchange . This conclusion is compatible also with the recent results on homogeneous and electrode electron exchange of ruthenium ammine complexes . In the heterogeneous electron-transfer case, rapid-scan cyclic voltammetric studies showed a correlation of electron-transfer rate with solvent longitudinal relaxation time, τ L , while deuterium NMR homogeneous self-exchange studies revealed no dependence of this kind, indicating a change to nonadiabatic from overdamped behavior upon going from the heterogeneous to the homogeneous process.…”
Section: Discussionsupporting
confidence: 86%
“…39 This conclusion is compatible also with the recent results on homogeneous and electrode electron exchange of ruthenium ammine complexes. 48 In the heterogeneous electron-transfer case, rapidscan cyclic voltammetric studies showed a correlation of electron-transfer rate with solvent longitudinal relaxation time, τ L , while deuterium NMR homogeneous self-exchange studies revealed no dependence of this kind, indicating a change to nonadiabatic from overdamped behavior upon going from the heterogeneous to the homogeneous process. This was also found to be the case in the present work and in recent NMR studies for homogeneous Fe(CN) 6 4-/3electron self-exchange (the extension of earlier 13 C NMR line-broadening studies 45 to water-glycerol mixtures 49 showed no change in the bandwidth due to the change of solution viscosity).…”
Section: Discussionmentioning
confidence: 98%
“…The coordination of the solvent to the redox center would perturb the intrinsic structure around the center and thus might contribute to the inner-sphere term, Δ G in ‡ . Similar DN effects have been reported for Ru II Ru III polyamine mixed-valence complexes, for which the effect has been interpreted by the redox-state-dependent rearrangements of hydrogen bonds between solvent and solute in the second coordination sphere by Curtis et al, and solvent−ammine donor−acceptor interactions by Crutchley et al19b…”
Section: Resultssupporting
confidence: 60%
“…Similarly, Meyer and co-workers have argued that extensive H-bonding to solvent by the −Ru III (NH 3 ) 5 group in [(bpy) 2 ClOs II (pz)Ru III (NH 3 ) 5 ] 4+ 6 mixes solvent character into d p (Ru III ), so decreasing electronic coupling to Os II across the pz bridge. Likewise, Curtis et al attribute trends in the optically induced intramolecular electron-transfer rates in bridged Ru III −Ru II complexes to redox-dependent H-bonding to solvent at Ru−NH 3 functions. If these arguments can be extended to inter molecular electron transfer of Ru−en rather than Ru−NH 3 complexes, then the anomalous strongly negative Δ V ex ⧧ for Ru(en) 3 3+/2+ in water may be tentatively explained in terms of a pressure-induced enhancement of solvation at the Ru II center, bringing the Ru II partner closer to a common Franck−Condon configuration prior to electron transfer.…”
Section: Discussionmentioning
confidence: 99%